2021
DOI: 10.3390/su132212612
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia Analysis of Spanish Female Role Models in Science, Technology, Engineering and Mathematics

Abstract: Horizontal segregation in the higher education framework is a problem that goes up in the work environment. Women are assuming traditional gender roles due to phenomena such as the threat of stereotyping, which prevents them from opting for higher studies in science, technology, engineering and mathematics (STEM). This research work arises within the project W-STEM, “Building the Future of Latin America: Involving Women in STEM”. The research aims to investigate women’s academic and professional development in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…The underrepresentation of women academics in STEM is referred to in the literature as horizontal segregation (O'Connor, 2020). The works of Smith et al (2017), Hutchins and Kovach (2019), Casad et al (2021), andVerdugo-Castro et al (2021) analyze the underrepresentation of female academics as researchers in STEM fields. In this area, Lendák-Kabók (2021) shows that gender stereotypes influence women's decisions regarding their academic careers and withdrawal from STEM areas, reflected in the underrepresentation documented in other studies and contexts.…”
Section: Thematic Category 1: Underrepresentation Of Women Academicsmentioning
confidence: 99%
“…The underrepresentation of women academics in STEM is referred to in the literature as horizontal segregation (O'Connor, 2020). The works of Smith et al (2017), Hutchins and Kovach (2019), Casad et al (2021), andVerdugo-Castro et al (2021) analyze the underrepresentation of female academics as researchers in STEM fields. In this area, Lendák-Kabók (2021) shows that gender stereotypes influence women's decisions regarding their academic careers and withdrawal from STEM areas, reflected in the underrepresentation documented in other studies and contexts.…”
Section: Thematic Category 1: Underrepresentation Of Women Academicsmentioning
confidence: 99%
“…A meta-analysis by Miller and colleagues [31] showed that, despite gradual improvement over the last fifty years, when children are asked to draw a scientist, the majority of drawings still depict White men. These impressions are not inaccurate as women and people of color are largely underrepresented in STEM fields in the United States and other western industrial nations [32]. Blickenstaff [33] writes that there is no singular reason why this is the case, but that it is a complex and multi-faceted problem.…”
Section: The Need For Diverse Stem Portrayalsmentioning
confidence: 99%
“…A nemek aránytalansága (a horizontális szegregáció) a felsőoktatás egyes területein nem egyedi probléma, számos országban fellelhető (Uchikoshi et al 2020, Verdugo-Castro et al 2021, Mercader -Duran-Bellonch 2021, Profiroiu -Nastacă 2018, azonban az egyik legjelentősebb negatív hatása az, hogy létrehoz és fenntart egy nemi hierarchiát a társadalomban (Kreimer 2004 idézi Profiroiu -Nastacă 2018). A nemi szegregáció korlátot szab a foglalkoztatási lehetőségeknek, erősíti a nemi sztereotípiákat, illetve egyenlőtlen erőviszonyokhoz vezet több területen.…”
Section: A Rejtett Tanterv Mint a Nemek Szerinti Horizontális Szegreg...unclassified